Macrophages and cardiac fibroblasts are the main producers of eotaxins and regulate eosinophil trafficking to the heart. Issue 12 (25th October 2016) - Diny, Nicola L.; Hou, Xuezhou; Barin, Jobert G.; Chen, Guobao; Talor, Monica V.; Schaub, Julie; Russell, Stuart D.; Klingel, Karin; Rose, Noel R.; Čiháková, Daniela
Abstract : We determined the pathway for eosinophil trafficking to the heart by examining a murine myocarditis model and heart biopsies from myocarditis patients. IL‐4 and IL‐13 induce production of eotaxins CCL11 and CCL24 by cardiac fibroblasts and macrophages. In response to eotaxins, eosinophils migrate to the heart via the receptor CCR3. Abstract : Cardiac manifestations are a major cause of morbidity and mortality in patients with eosinophil‐associated diseases. Eosinophils are thought to play a pathogenic role in myocarditis. We investigated the pathways that recruit eosinophils to the heart using a model of eosinophilic myocarditis, in which experimental autoimmune myocarditis (EAM) is induced in IFNγ −/− IL‐17A −/− mice. Two conditions are necessary for efficient eosinophil trafficking to the heart: high eotaxin (CCL11, CCL24) expression in the heart and expression of the eotaxin receptor CCR3 by eosinophils. We identified cardiac fibroblasts as the source of CCL11 in the heart interstitium. CCL24 is produced by F4/80 + macrophages localized at inflammatory foci in the heart. Expression of CCL11 and CCL24 is controlled by Th2 cytokines, IL‐4 and IL‐13. To determine the relevance of this pathway in humans, we analyzed endomyocardial biopsy samples from myocarditis patients. Expression of CCL11 and CCL26 was significantly increased in eosinophilic myocarditis compared to chronic lymphocytic myocarditis and positively correlated with the number of eosinophils. Thus, eosinophil trafficking to the heart is dependent on the eotaxin‐CCR3 pathway in a mouse model of EAM and associated with cardiac eotaxin expression in patients with eosinophilic myocarditis. Blocking this pathway may prevent eosinophil‐mediated cardiac damage.